Video-based flipped classroom technique for word processing: Effects on gender performance of business education students in universities - Anyigor-Ogah , Augustina Chinweoke (American Journal of Education and Learning, 2025)
The study’s purpose is to determine the effect of video-based flipped classroom techniques on the mean performance of male and female students taught Word Processing using the flipped classroom technique. A quasi-experimental design was used. The design involved a pre-test and post-test non-equivalent control group design. The population for the study consisted of 87 fourth-year undergraduate students from the business education department across seven public universities offering Word Processing in the Southeast. The sample size was 33 students (12 males and 21 females) selected using purposive sampling techniques. Results revealed that both male and female students showed below-average performance in the pretest but demonstrated a significant difference in the actual mean in the post-test. Both groups displayed significant improvement in Word Processing. Additionally, the results indicated no significant difference between the mean achievement scores of male and female students taught Word Processing using the video-based flipped classroom technique. It was concluded that the video-based flipped classroom technique did not appear to have a differential effect on male and female students’ achievement in Word Processing. The practical implication is that Word Processing lecturers should embrace the flipped classroom technique due to its advantages in increasing students’ achievement in Word Processing, regardless of gender.